(untitled) (Revista INTEREDU11, 2023)
The empirical and contextual evidence in which the following article is framed highlights the impact of the development of didactic strategies focused on promoting interculturality related to reading comprehension. For such reason, this research seeks to offer a pedagogical proposal made in the subject Lenguaje y Comunicación, whose objective has been to strengthen the development of inferential ability, as well as to materialize critical interculturality, for the purpose of transforming the perception that 5th grade students have regarding the Mapuche people, specifically. Given the mixed nature of this research, a case study has been conducted to analyze the reading comprehension process, in depth, from two pedagogical interventions. To analyze the collected data, a discourse and content analysis tool has been used which has allowed to reveal hidden meanings in relation to the configuration the participants had about the Mapuche people. Among the results obtained, it can be highlighted that not only did they manage to strengthen their level of inferential understanding, but also that they have been able to change their perception of the Mapuche people.